Late-Victorian Girls and their Manuscript Magazines Girlhood and Textual Transformation in Britain, 1860-1900 - Burke, Lois (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XI, 136 p. 15 illus., 8 illus. in color.